Moral Degradation in an Educational Milieu: Roles of Guardian in Fixing Morality of Students - Zulkipli Lessy; Nurul Ahwat Rantekata; Miftahur Rohman; Heru Juabdin Sada (AL-ISHLAH: Jurnal Pendidikan, 2024)
Moral degradation among students is a common phenomenon in the educational milieu; thus, guardians have a significant role to play in handling it for their future welfare. This study aims to (1) investigate the efforts of the Islamic residential school guardians in dealing with moral degradation among the students; (2) identify the obstacles they encounter and provide facilitation for dealing with the moral degradation; (3) explore the impact of the guidance given by the guardians to the students. The research is a qualitative study with a phenomenological descriptive approach. The sampling was purposive. The informants were two guardians at the pesantren, each serving as a teacher of guidance and counselling, coordinator of the student council, and five students who experienced moral decline. The results indicate that the guardians build up relationships between the school and students, instill moral values based on religious guidance, prevent the negative effect of globalization on the school, and facilitate communication with the parents if the students do something wrong. The results also show that a highly effective learning environment at the pesantren and the effective role of the student council can support and rehabilitate moral decadence. The results further reveal the impacts of the guidance on students, such as the current cohort of students, who tend to be more disciplined compared to the previous cohort. However, the lack of representative counselling rooms and some counselling teachers who are inattentive to students’ behavior is disadvantageous for rehabilitation.